Agricultural fertilization with poultry manure results in persistent environmental contamination with the pathogen Clostridioides difficile. (10th June 2021) - Frentrup, Martinique; Thiel, Nadine; Junker, Vera; Behrens, Wiebke; Münch, Steffen; Siller, Paul; Kabelitz, Tina; Faust, Matthias; Indra, Alexander; Baumgartner, Stefanie; Schepanski, Kerstin; Amon, Thomas; et al.
Summary: During a field experiment applying broiler manure for fertilization of agricultural land, we detected viable Clostridioides (also known as Clostridium ) difficile in broiler faeces, manure, dust and fertilized soil. A large diversity of toxigenic C . difficile isolates was recovered, including PCR ribotypes common from human disease. Genomic relatedness of C . difficile isolates from dust and from soil, recovered more than 2 years after fertilization, traced their origins to the specific chicken farm that had delivered the manure. We present evidence of long‐term contamination of agricultural soil with manure‐derived C . difficile and demonstrate the potential for airborne dispersal of C . difficile through dust emissions during manure application. Clostridioides genome sequences virtually identical to those from manure had been recovered from chicken meat and from human infections in previous studies, suggesting broiler‐associated C . difficile are capable of zoonotic transmission.